COVID-19 awareness among undergraduates in a private university - Yi-Fan Tan; Lee-Yeng Ong; Meng-Chew Leow (Intelektual Pustaka Media Utama, 2022)
Since the first declaration of the coronavirus disease 2019 (COVID-19) outbreak in December 2019, the pandemic has brought some significant lifestyle changes among the people across the globe. There might be some underestimation in the severity level of COVID-19 among younger people, specifically around the age group of undergraduates. This study evaluated the awareness level of Malaysian undergraduates towards COVID-19 in Malaysia via an online survey hosted in a COVID-19 awareness roadshow event. This study highlighted the importance of high awareness level of the pandemic among undergraduates and their impact towards managing the spread of the pandemic to the vulnerable population. The respondents were information technology (IT) undergraduates from Multimedia University Melaka Campus, Malaysia. The overall awareness level of the undergraduates is high. Most respondents had a clear understanding on the effects of personal hygiene and personal protective equipment to avoid getting infected with COVID-19, as well as where to go if they got infected with the coronavirus. Most respondents also showed decent knowledge in identifying the basic symptoms of COVID-19. These findings give an insight into the COVID-19 awareness level among undergraduates and may help the policymakers and university managements to control the spread of COVID-19 and other emerging infections.